Biomarkers for Components of Dietary Protein and Carbohydrate with Application to Chronic Disease Risk in Postmenopausal Women. Issue 4 (7th January 2022) - Prentice, Ross L; Pettinger, Mary; Zheng, Cheng; Neuhouser, Marian L; Raftery, Daniel; Gowda, G A Nagana; Huang, Ying; Tinker, Lesley F; Howard, Barbara V; Manson, JoAnn E; Van Horn, Linda; Wallace, Robert; et al.
ABSTRACT: Background: We recently developed protein and carbohydrate intake biomarkers using metabolomics profiles in serum and urine, and used them to correct self-reported dietary data for measurement error. Biomarker-calibrated carbohydrate density was inversely associated with chronic disease risk, whereas protein density associations were mixed. Objectives: To elucidate and extend this earlier work through biomarker development for protein and carbohydrate components, including animal protein and fiber. Methods: Prospective disease association analyses were undertaken in Women's Health Initiative (WHI) cohorts of postmenopausal US women, aged 50–79 y when enrolled at 40 US clinical centers. Biomarkers were developed using an embedded human feeding study ( n = 153). Calibration equations for protein and carbohydrate components were developed using a WHI nutritional biomarker study ( n = 436). Calibrated intakes were associated with chronic disease incidence in WHI cohorts ( n = 81, 954) over a 20-y (median) follow-up period, using HR regression methods. Results: Previously reported elevations in cardiovascular disease (CVD) with higher-protein diets tended to be explained by animal protein density. For example, for coronary heart disease a 20% increment in animal protein density had an HR of 1.20 (95% CI: 1.02, 1.42) relative to the HR for total protein density. In comparison, cancer and diabetes risk showed little association with animal protein density beyond that attributable to total protein density. Inverse carbohydrate density associations with total CVD were mostly attributable to fiber density, with a 20% increment HR factor of 0.89 (95% CI: 0.83, 0.94). Cancer risk showed little association with fiber density, whereas diabetes risk had a 20% increment HR of 0.93 (95% CI: 0.88, 0.98) relative to the HRs for total carbohydrate density. Conclusions: In a population of postmenopausal US women, CVD risk was associated with high-animal-protein and low-fiber diets, cancer risk was associated with low-carbohydrate diets, and diabetes risk was associated with low-fiber/low-carbohydrate diets.